Análise de ecoeficiência para escolha de soluções de produção mais limpa: o caso de uma indústria de tintas - Molinari, Marcelo Alessandro (2010)
The objective of this research is to develop an ecoefficiency analysis methodology for decision-making between cleaner production (CP) techniques. This research seeks a contribution to scientific advances related to CP using the existing knowledge in the field of environmental management systems. The problem of the research raises the following question: how will a methodology be to assist in decision-making between different CP techniques? Three CP techniques were suggested to be evaluated based on a bibliographic research and also a field research. The result of this research is a graphical tool that provides the visual information needed to compare CP techniques in terms of economic cost and environmental risk